“STUDY WEIR MEJANG NEW MIAU VILLAGE DISTRICTS KONGBENG EAST KUTAI DISTRICT EAST KALIMANTAN PROVINCE " - SANJAYA, MUHAMMAD (KURVA S JURNAL MAHASISWA, 2020)
A weir is a river transverse structure that functions to elevate the water level so that it can be taken and channeled through the building. Permanent Weir of Miau Baru Village, Kongbeng Sub district, East Kutai Regency, East Kalimantan is the source of water from Mejang to supply raw water, especially for the benefit of the agricultural sector with an area of 1276 Ha. The weir in Mejang River Basin (DAS) is to be re-analyzed to discover the effectiveness of the weir. So it needs to be reviewed by analyzing the capacity and stability of the Mejang Permanent Weir by using the hundred year period (Q100) flood discharge, with a watershed area of 23.37 km2 . This research was conducted to determine whether the stability of the Mejang Permanent Weir is safe against the forces that work with discharge (Q100) and the capacity in millions of cubicle. This study uses secondary data in the form of daily rainfall data for 10 years from 3 stations. The Mejang Weir Study in Miau Baru Village, Kongbeng Sub district, East Kutai Regency is determined to re-analyze the return plan (Q100) discharge capacity, the capacity of the weir, and the stability of the weir to the forces calculated are the forces due to the weights' own weights, lift force / uplift pressure, forces hydrostatic in weir, Force due to active and passive soil pressure, Earthquake force, Review of rolling, Review of shear and Review of carrying capacity of the soil. The results showed that 100-year period rainfall with Log-Pearson Type III (mm) method = 493.88 mm obtained fifty-year period flood discharge (Q100) with the Nakayasu Method = 249.65 m3 / sec. The dimensions of the weir are safe for the force due to weir's own weight, lift / uplift pressure, the hydrostatic force in the weir, the force due to active and passive earth pressure, earthquake force, review of the bolt, review of the shear, review of the carrying capacity of the soil and the forces works well during normal water conditions and flood water conditions.